Open Secret - Strategies for Hope (Television for Development, 2015)
People facing up to HIV and AIDS in Uganda. How civil society organisations, political leaders and government agencies breached the wall of silence surrounding AIDS, leading to reduced HIV prevalence in Uganda. Produced by Television for Development for the Strategies for Hope Trust.
Free